2009
DOI: 10.1002/hup.1071
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in social competence in patients with schizophrenia: a pilot study using a performance‐based measure using virtual reality

Abstract: Our results suggest that the VRFAS is strongly sensitive to changes in social competence and thus especially beneficial in short-term clinical trials. In addition, atypical antipsychotics can improve social competence and differentially improve receptive skills and expressive skills in schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 31 publications
0
13
0
1
Order By: Relevance
“…10 Initial findings from South Korea suggest that VR scenarios may be useful in evaluating social skills and emotions arising from social interactions in patients with schizophrenia. 21,22 Conclusion VR seems an acceptable and sufficiently realistic method to use in patients with first episode psychosis. It offers a unique way to expose individuals to controlled social environments.…”
Section: Previous Researchmentioning
confidence: 97%
“…10 Initial findings from South Korea suggest that VR scenarios may be useful in evaluating social skills and emotions arising from social interactions in patients with schizophrenia. 21,22 Conclusion VR seems an acceptable and sufficiently realistic method to use in patients with first episode psychosis. It offers a unique way to expose individuals to controlled social environments.…”
Section: Previous Researchmentioning
confidence: 97%
“…Patients who switched from either olanzapine or risperidone to aripiprazole manifested improvements in subjective well-being 2. Our research group demonstrated that the usefulness of aripiprazole in patients with schizophrenia included the improvement of social competence,3 which refers to overall capacity to solve life problems and achieve instrumental and affiliative goals 4. These advantages of aripiprazole may be related to its distinctive pharmacological profile as a partial agonist of D 2 and HT 1A receptors and as an antagonist of 5-HT 2A and 5-HT 2C receptors 5.…”
Section: Introductionmentioning
confidence: 75%
“…Four parameters representing a distinct functional skill were obtained; initiation (the response latency to the avatar's voice for the receptive skills phase and to the avatar's question for the expressive skills phase), duration (the percentage of time spent watching the avatar), proxemics (the average distance from the avatar), and eye contact (the average angle of head orientation from the avatar's eyes). In a 6-week, randomized, open-label, and flexible dose study for 24 patients with paranoid schizophrenia and 15 healthy controls (Park et al, 2009c), there was a significant difference in the VRFSA between the patients and the healthy controls (p < 0.05). Significant treatment skills phase group interaction effect was found, and particularly, compared with risperidone, aripiprazole was more effective in improving social skills competency.…”
Section: Expanded Uses Of Virtual Reality-based Social Skills Assessmmentioning
confidence: 97%
“…Not surprisingly, the author's research team devised the virtual reality system to provide an automatic assessment of patients' performance (Fig. 5), which was named the virtual reality functional skills assessment (VRFSA) (Park et al, 2009c). The VRFSA consisted of six virtual reality scenarios that were produced to represent common conversational situations.…”
Section: Expanded Uses Of Virtual Reality-based Social Skills Assessmmentioning
confidence: 99%